A literature review of the spider monkey, Ateles sp., with special focus on risk for extinction - Takahashi, Julia (SLU/Dept. of Animal Environment and Health (until 231231), 2008)
This literature review summarizes and clarifies taxonomy, geographic distribution, status, habitat and food choice, threats, social organization and reproduction of spider monkeys, genus Ateles. The aim of the study is to asses why spider monkeys are vulnerable for extinction and discuss possible conservation actions. Spider monkeys live in subtropical and tropical rainforest in the Neotropic ecoregion from southern Mexico to northern Bolivia. At the time sixteen species and subspecies are accepted, of which thirteen are considered as endangered, vulnerable or critically endangered at the IUCN's red list; only three of them are at least concern. They are one of the largest New World monkeys. They travel fast with assistant by their prehensile tail, have large home ranges and prefer undisturbed old rainforest as habitat and are considered to be ripe-fruit specialists, although they have been seen to eat larger amount of unripe fruits and leaves and can temporally shift habitat in search for food. Many different kinds of fruits are eaten depending on the availability and season but species from Moraceae, Myristicaeae and Burseraceae family are reported from several sites. They are also important seed dispersals, which may play a role in the rainforest composition in long terms. They live in a fission-fusion system in sex segregated social groups, where small subgroups join and split. Reproductively they mature late and have long interbirth interval. Major threats are habitat reduction and not least hunting. Many of the spider monkeys characteristics and demand for special and large habitat and suitable food makes it very vulnerable for extinction, and all this information is important for the conservation of the species.